Structure characteristics and combustibility of carbonaceous materials from blast furnace flue dust. (5th September 2016) - Zhao, Di; Zhang, Jianliang; Wang, Guangwei; Conejo, Alberto N.; Xu, Runsheng; Wang, Haiyang; Zhong, Jianbo
Highlights: The combustion properties of carbonaceous materials in dust were investigated. The mico-structures of carbon materials in dusts were exemplified distinctly. The carbon activity differences were depended on their diverse mico-structures. Kinetic parameters were obtained in the method of nonlinear least-squares fitting. VM and RPM model for carbonaceous materials in dust and their pyrolytic coke. Abstract: The structure characteristics and combustibility of carbonaceous materials from gravitational dust and bag dust of hop pocket were investigated using laser particle size analyzer, scanning electron microscopy, X-ray Diffraction, polarization microscopy and thermogravimetric analysis. Simultaneously, coal char and pyrolyzed coke were used as comparison. The acid-washing process was performed to avoid the effects of inorganic matters and beneficiate carbonaceous materials in dust. Three representative gas-solid reactivity models, random pore model, volume model, and unreacted core model were applied to study kinetic parameters. Results showed that carbonaceous materials in dust were mainly originated from coke fines and those in bag dust of hop pocket presented a high reactivity, mainly attributed to its more disordered crystalline structure and higher porosity. It was concluded from kinetic analysis that volume model was the best model for simulating the combustion process. The activation energies of bag dust of hop pocket, gravitational dust and coke calculated by this model were 118.6 kJ/mol, 141.7 kJ/mol, 156.1 kJ/mol, respectively, indicating carbon in bag dust of hop pocket are easily reacted with oxygen and proving its high combustibility.